Association between occupational stress and mental health in an automobile manufacturing factory in Iran - Sahar Eftekhari; Leila Karimi; Seyed Akbar Sharifian; Omid Aminian; Seyed Ramin Rasooli; Ghasem Zia (International Journal of Occupational Safety and Health)
Introduction: This study aimed to assess the relationship between occupational stress and the symptoms of anxiety, depression, and stress among the employees of an automobile manufacturing factory in Iran.